2020
DOI: 10.3389/fmicb.2020.00703
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21 Aggravates Herpes Simplex Virus Epithelial Keratitis by Attenuating STING-IRF3-Mediated Type I Interferon Signaling

Abstract: Herpes simplex virus-1 (HSV-1) is the leading cause of infectious blindness in the developed world. HSV-1 infection can occur anywhere in the eye, and the most common presentation is epithelial keratitis. In the HSV epithelial keratitis mice model, we detected the expression of TRIM21 and then investigated the clinical relationship between TRIM21 and HSV epithelial keratitis by silencing TRIM21. Through the clinical scores and histopathology examination, we found that TRIM21 can effectively reduce the severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Alternatively, UV irradiation can induce a variety of pro‐inflammatory cytokines via infiltrated immune cells which coordinate to control skin homeostasis. For example, UVB‐induced NF‐κB activation via STING leads to the production of type I IFN from inflammatory monocytes, 61 and confers a protective function to decrease pro‐inflammatory genes and inflammation response in the skin 61,62 . Taken together, it still needs to decipher the detailed cellular events of PARP‐1 in UV‐stressed skin tissues that can be the direct actions in dermal immune cells and the intricate cellular cross talk in the stressed microenvironment between keratinocytes and immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, UV irradiation can induce a variety of pro‐inflammatory cytokines via infiltrated immune cells which coordinate to control skin homeostasis. For example, UVB‐induced NF‐κB activation via STING leads to the production of type I IFN from inflammatory monocytes, 61 and confers a protective function to decrease pro‐inflammatory genes and inflammation response in the skin 61,62 . Taken together, it still needs to decipher the detailed cellular events of PARP‐1 in UV‐stressed skin tissues that can be the direct actions in dermal immune cells and the intricate cellular cross talk in the stressed microenvironment between keratinocytes and immune cells.…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al (2018) reported that ZIKV-induced NF-κB activation promoted the expression of Drosophila STING and triggered autophagy to clear the virus. It is noteworthy that during HSV-1 infection, autophagy activation rather than type I IFN signaling seems to be the main effector function of STING in regulating viral infection ( Tan and Xia, 2020 ; Yamashiro et al, 2020 ). A similar function of STING-dependent autophagy was also found in infections with pathogenic bacteria such as M. tuberculosis , Listeria innocua , and Staphylococcus aureus ( Watson et al, 2012 ; Moretti et al, 2017 ).…”
Section: Cgas–sting Signaling Induces Type I Interferon Production and Triggers Autophagymentioning
confidence: 99%
“…The tripartite motif protein 21 (TRIM21) plays a regulatory role in innate immune responses by interacting with antiviral factors. Studies have shown that TRIM21 has a wide range of regulatory effects on IRF3-mediated type I IFN ( Stacey et al., 2012 ; Tan and Xia, 2020 ). To verify interaction between MGF360-14L and TRIM21, HEK293T cells and PK15 were co-transfected with MGF360-14L-Flag and TRIM21-HA plasmids, respectively.…”
Section: Resultsmentioning
confidence: 99%